2022
DOI: 10.1590/0103-8478cr20210547
|View full text |Cite
|
Sign up to set email alerts
|

Performance, meat quality, and lipidemia of meat-type quails fed with diets containing essential oils

Abstract: This study evaluated the effect of essential oil (ESOL) of Mentha piperita and Melaleuca alternifolia on meat-type quails. To examine performance, a completely randomized design was used, with four treatments and eight repetitions each, using seven birds per repetition. To assess lipidemia, a completely randomized design in a 4 × 2 factorial scheme was used, with four treatments and two collection conditions using eight repetitions and one bird per repetition. Weight gain, feed intake, feed conversion, carcass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…After weighing on day 42, all birds were fasted for 8 h. Then, the birds were weighed individually, desensitized by electronarcosis, bled and slaughtered. The birds were weighed at the following times: desensitization; after bleeding, and eviscerated without head, feathers, and legs to determine the carcass yield [ 3 ] (CY). Then, the carcasses were manually eviscerated, washed with running a water and ice solution (1:1) and stored in a cold chamber (5 °C) onset of rigor mortis (for 24 h).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…After weighing on day 42, all birds were fasted for 8 h. Then, the birds were weighed individually, desensitized by electronarcosis, bled and slaughtered. The birds were weighed at the following times: desensitization; after bleeding, and eviscerated without head, feathers, and legs to determine the carcass yield [ 3 ] (CY). Then, the carcasses were manually eviscerated, washed with running a water and ice solution (1:1) and stored in a cold chamber (5 °C) onset of rigor mortis (for 24 h).…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] It was shown that the oil may promote an improved conversion of the diet and consequently productive performance of the quails. [3,4] The terms fat, oil, or lipid are generically used for a large number of compounds which show insolubility in water and solubility in organic solvents. Lipids are foods sources that are most susceptible to oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations